An examination of tax service quality with the use of online tax systems: A structural equation modelling analysis - Song, Kosal (Edelweiss Applied Science and Technology, 2025)
This study investigates the relationships between Tax Quality Service (TQS), Perceived Ease of Use (PEOU), and online tax system usage (OTSU) using Structural Equation Modeling (SEM). The research tested four hypotheses (H1–H4) to explore both direct and indirect effects among these variables. Findings reveal that TQS has a strong and significant direct impact on OTSU (path coefficient = 0.784, p < 0.001), suggesting that high-quality service delivery positively influences system usage. TQS also significantly affects PEOU (path coefficient = 0.837, p < 0.001), indicating that better service quality enhances users’ perception of system usability. Furthermore, PEOU has a very strong direct effect on OTSU (path coefficient = 0.926, p < 0.001), highlighting the crucial role of system usability in driving user adoption. Importantly, PEOU was also found to mediate the relationship between TQS and OTSU (indirect effect = 0.775, p < 0.001), demonstrating that ease of use serves as a key channel through which service quality impacts system usage. These results support a theoretical model that integrates service quality and technology acceptance, emphasizing the need to improve both service delivery and system usability to increase user engagement and successful technology adoption.